The corporate parenting advantage, revisited - Feldman, Emilie R. (Strategic Management Journal, 2021)
Abstract Research Summary This paper investigates the corporate parenting advantage, the extent to which corporate parents improve the performance of their subsidiaries. Despite the importance of this concept for corporate strategy, researchers have yet to quantify it empirically. I measure the corporate parenting advantage by comparing the performance of utilities that were legally classified into one of two types of holding companies: regulated holding companies, which faced limits on their ability to parent, and exempt holding companies, which did not. I find that observationally similar utilities that were owned by exempt holding companies outperform utilities that were owned by regulated holding companies, and that this performance differential attenuates once the legal restrictions on parenting were lifted. These results provide the first large‐scale empirical evidence of the corporate parenting advantage. Managerial Summary By how much do corporate parents improve the performance of their subsidiaries? Despite the importance of this question of the “corporate parenting advantage,” it does not yet have a clear answer. In this paper, I measure the corporate parenting advantage by comparing the performance of utilities that were legally grouped into one of two types of holding companies: regulated holding companies, which faced limits on their ability to parent, and exempt holding companies, which did not. I find that comparable utilities that were owned by regulated holding companies have lower return on assets than utilities that were owned by exempt holding companies, and that this performance difference disappears once the legal restrictions on parenting were lifted. These results provide evidence of the corporate parenting advantage.